Contact angle measurement of SAC 305 solder: numerical and experimental approach - Rodrigues, Nelson Ricardo Pereira (2016)
The solder process comprises the ability of a melted alloy to flow or spread on a substrate for the formation of a metallic bond driven by the physical–chemical properties of the system. Thus, the study of wetting behaviour is an important step in the characterisation of solder alloys and requires the discussion of different parameters that affect the solder junctions. The main objective of this work is to use a CFD study to determine the influence of several parameters in the melting shape obtained with a solder, of the SAC 305 type and compare the numerical results with experimental data. The computational model was implemented in ANSYS Fluent® and the simulations were carried out involving the melting of a material using the Volume of Fluid (VOF) method to capture the solidification/melting interfaces based on an enthalpy-porosity approach. The results show that shape of the melted solder is greatly influenced by the contact angle and, to a smaller extent, by the surface tension. It was also concluded that it is possible to accurately predict the shape of the melted solder using computational fluid dynamic tools in complement to the experimental validation.